Future of work and education in 21st century. Coworking as learning space - Glenda Galeotti (Formare, 2019)
The transformation of the labour market has caused rapid unavoidable effects on educational and training needs. As a part of the debate on the future of work, learning and skills in the 21st century, this contribution focuses on learning processes in coworking as shared workplaces where it is possible to combine different professional skills in a productive, social and learning environment. In fact, coworking spaces can interpret the changes in our society, offering an alternative perspective on labour based on collaboration and meaningful connections between people, as well as self-directed, self-regulated, and socially integrated educational pathways.